Fazer-se “universitário(a)”: pelas ações afirmativas e políticas de diversidade e inclusão dos Institutos Federais de Educação, Ciência e Tecnologia da Bahia - Santos, Roberto Carlos Oliveira dos (2025)
This Doctoral Thesis focuses on Affirmative Action Public Policies implemented in the Federal Network of Technological Education (RFEPCT) by the Diversity and Inclusion Policies (PDI), which are the normative institutional instruments of the Federal Institutes (IFs) for this purpose. After the implementation of the PDI in 2012, in the RFEPCT teaching diversified racially and socioeconomically, especially in higher education. Therefore, these transformations require identifying students' perceptions about the impact and repercussions of affirmative actions on their “university” becoming and on their sociocognitive strategies for academic permanence, especially when they enter careers of greater social prestige, as in the case of the participants of this study, in engineering courses. Thus, the main objective was to analyze the material and symbolic mechanisms that contribute to the academic performance of students entering higher education through racial quotas. Based on the analytical categories of Bourdieu and Coulon, the interconnection of the sociocultural, educational and historical conditions of students was understood based on the intersection of elements of racial identity, social origin and educational experience. Reis and Oliveira pointed out perspectives to perceive dimensions of permanence as a time of duration and change, in this sense, permanence is, therefore, the moment that transforms the future. Becoming a university student through quotas, as well as every initiation rite, is a construction to be followed along paths that reveal mysteries of cognitive development and, when anchored in identity belonging, supports maturity for making academic and professional decisions, many of which are influenced by perceptions of the world originating not only from family ties of consanguinity, but from the community experiences of those who do not walk alone. The methodological approach is based on empirically based qualitative research with the contribution of the following data collection instruments: focus group, semistructured interviews and documentary analysis. The data collected were analyzed in light of the Theory of Discourse Analysis. The research participants are 20 quota students, who occupy racial quotas in Engineering courses at two Federal Institutes of Education, Science and Technology, based in the State of Bahia. Therefore, a study like this one can contribute with its results to understanding new configurations of learning management and scientific knowledge management of quota students inside and outside the academic environment, as well as subsidize the institutional improvement of student monitoring and assistance instruments for possible adjustments and/or improvement of Affirmative Action Policies for diversity and inclusion.